The Arabs of the Ottoman Empire, 1516-1918 a social and cultural history - Masters, Bruce Alan (Cambridge University Press, 2013)
The Ottomans ruled much of the Arab World for four centuries. Bruce Masters's work surveys this period, emphasizing the cultural and social changes that occurred against the backdrop of the political realities that Arabs experienced as subjects of the Ottoman sultans. The persistence of Ottoman rule over a vast area for several centuries required that some Arabs collaborate in the imperial enterprise.